Collembolan communities in a sustainable system for production of woody biomass for energy: abundance and diversity of morphospecies. - Santos, Sónia A.P. (2011)
Woody biomass for energy obtained from short rotation woody crops (SRWC) needs to be managed in a sustainable way, thus allowing ecosystem conservation. However, there is a gap in our knowledge concerning the effects of these crops on soil organisms, of which collembolans represent a good indicator of soil quality. On the other hand, soil biological sciences are strongly affected by the taxonomic skill crisis, with many groups of soil animals suffering from a taxonomic impediment in terms of identification. This problem can be reduced by using a para-taxonomic approach where morphospecies can be used as surrogates of taxonomic species. The objective of this work was to study the structure of collembolan communities in a SRWC experimental field using morphospecies. Abundance, richness, evenness and diversity indexes were used to describe the structure of the collembolan community and species accumulation curves were computed to estimate species richness in the study area. Prior to the installation of the SRWC, 106 soil samples were collected at each defined sampling point (distributed along 14 transects) using a soil core (5 cm diameter x 10 cm depth). In the laboratory, collembolans were extracted from the soil (using a McFadyen apparatus), sorted, counted and finally identified to morphospecies level. The number of morphospecies observed was 34, representing a total abundance of 3221 collembolans. The Simpson Diversity Index and richness were 27and 34, respectively. The species accumulation curves showed that the estimated number of morphospecies was 38.